Designing a Visual Novel Game in Nusantara Folklore 'The Origin of Lake Toba' using Renpy Visual Novel Engine - Noprita Elisabeth S; Rani Hermita (SISFOTENIKA, 2021)
Public knows about the folklore of the archipelago in Indonesia through stories told directly by parents and their families, passed down orally from parents to children and their ancestors to future generations. Likewise, the folklore of the origin of Lake Toba. The folklore of the archipelago seems to be slowly disappearing because it is only passed down orally and is less desirable and does not rule out being forgotten and extinct. This is what makes the writer decide to conduct research on the folklore of the archipelago through the media of games, namely visual novels with the story of the origin of Lake Toba as the object. The researcher wants to make an application in the form of animation with the help of a program that wants to be enjoyed by many people and can also be used as a learning medium.The game application that will be produced will later be made using the Ren'Py Novel Visual Engine application and the research method that the author will use is an extreme programming as a management system with the following stages: Exploration Phase, Planning Phase, Iteration Phase, Production Phase, Maintenance Phase and Final Publication Stage ( Death Phase), with the existing tools can make the application of the story of the origin of Lake Toba well, then for future research to make it in a 3-dimension version